Bi-directional evolutionary topology optimization for designing a neutrally buoyant underwater glider. Issue 8 (3rd August 2018) - Tang, Tengfei; Li, Baoren; Fu, Xiaoyun; Xi, Yi; Yang, Gang
ABSTRACT: An underwater glider is a type of autonomous profiling instrument platform used for gathering data to explore the ocean. Having a neutrally buoyant glider hull is one way to improve the glider's endurance with a passive compensation for buoyancy change. This article applies the bi-directional evolutionary structural optimization (BESO) method to the optimization of an underwater glider hull, based on two materials. Firstly, the method for determining the glider's neutral buoyancy is carried out. Secondly, the optimization problem is defined and the optimization procedure is presented. In the BESO procedure, the original design area elements with low strain energy are iteratively switched from high-value materials to low-value materials until a prescribed fraction is reached. Finally, an optimal underwater glider design is generated and the result demonstrates a reasonable material distribution of the neutrally buoyant glider hull. A 26.4% buoyancy adjustment is achieved and the mass of the glider is decreased by 31%.